The Role of Project Management Offices in Managing Organizational Change for Strategy Execution Effectiveness - Tourista, Meiko; Nugraha, Arlies Meta; Erfiyana, Ev (IJOSMAS, 2025)
This study addresses the persistent challenge of strategy execution effectiveness in organizations, by investigating the evolving role of Project Management Offices (PMOs) in managing organizational change. Traditionally viewed as governance entities focused on project monitoring and compliance, PMOs are increasingly repositioning themselves as strategic enablers that integrate project governance with change management to bridge the gap between strategy formulation and execution. Through a comprehensive literature review, this research develops a conceptual framework positioning PMO services as antecedents, organizational change management as a mediating factor, and strategy execution effectiveness as the ultimate outcome. The findings reveal that embedding organizational change management into PMO functions significantly enhances an organization’s capacity to realize strategic goals, emphasizing the people dimension of change as crucial to sustaining strategic initiatives. While limited by its descriptive methodology and reliance on secondary data, this work offers valuable theoretical insights and practical implications for organizations seeking to harness PMOs as catalysts for strategic transformation. It underscores the imperative for PMOs to adopt a service-provider mindset that proactively addresses the people side of change, advocating for a symbiotic partnership between PMO professionals and change managers. Ultimately, this research serves as a call to action for senior leaders and practitioners to reconceptualize PMOs not merely as administrative units but as vital agents of strategic change, where successful execution is as much about people engagement as it is about technical rigor.